Plant translational reprogramming for stress resilience - Son, Seungmin; Park, Sang Ryeol (Frontiers in Plant Science, 2023)
Organisms regulate gene expression to produce essential proteins for numerous biological processes, from growth and development to stress responses. Transcription and translation are the major processes of gene expression. Plants evolved various transcription factors and transcriptome reprogramming mechanisms to dramatically modulate transcription in response to environmental cues. However, even the genome-wide modulation of a gene’s transcripts will not have a meaningful effect if the transcripts are not properly biosynthesized into proteins. Therefore, protein translation must also be carefully controlled. Biotic and abiotic stresses threaten global crop production, and these stresses are becoming more severe due to climate change. Several studies have demonstrated improved plant resistance to various stresses through modulation of protein translation regulation, which requires a deep understanding of translational control in response to environmental stresses. Here, we highlight the translation mechanisms modulated by biotic, hypoxia, heat, and drought stresses, which are becoming more serious due to climate change. This review provides a strategy to improve stress tolerance in crops by modulating translational regulation.